(untitled) (Research, Society and Development, 2023)
Toxoplasmosis, an anthropozoonosis caused by the protozoan Toxoplasma gondii, is a frequent infection worldwide. In most cases, it does not have major repercussions for the patient, except in immunosuppressed individuals and fetuses, which may have serious sequelae. The main source of maternal infection is the ingestion of the parasite in the form of bradyzoite, contained in meat or its raw or undercooked products. Fetal transmission is directly related to the gestational age at which the maternal infection occurred, with the highest risk in the third trimester. It is known that infection by the protozoan in children can present in different ways, ranging from death after birth, survival with brain damage or mild to subclinical disease, often with ocular alteration. The study was carried out for 1 (one) year, with analysis of medical records, with a qualitative and quantitative descriptive statistical analysis of children born between the years 2019 to 2021 were diagnosed with congenital toxoplasmosis. The method of selection of patients was done through the diagnosis of confirmed congenital toxoplasmosis to which patients are accompanied at the Specialized Center for Infectious and Parasitic Diseases (CEDIP) in the city of Cascavel/PR. The study sought to evaluate clinical changes in children with congenital toxoplasmosis.